Becoming a real musician : inspiration and guidance for teachers and parents of musical kids - Woody, Robert H. (Rowman & Littlefield, 2019)
"Nobody is born a musician. Rather, people become musical. They do so through the right experiences as children, and with the right kind of support from the adults in their lives. Most teachers and parents believe that music can be a powerful gift to kids. Ideally, it becomes a lifelong gift, rather than merely a pastime of childhood to be reminisced about later. Unfortunately, not all music educational experiences produce a lasting musicianship. Becoming a real musician shares how learning experiences can be made more relevant, practical, and real world for young people studying music. With such experiences, kids can be on their way to becoming real musicians, defined as people whose musical skills allow them to lead musically active lives, whether music making is their profession of a personally fulfilling part of their leisure time"--back cover.